The Evolution of the Elementary Science Program in the Cleveland Public Schools. - Melrose, Mary (Science Education, 1933)
The article presents the author's opinion on the introduction of elementary science program in the public schools in Cleveland, Ohio. Endeavors were made to construct a course of study based on the fundamentals of children's natural interests. The author suggests that the growth of science curriculum should have a natural unfolding and not a forced development. The Science Curriculum Center in Cleveland has developed some outstanding science teachers. The author describes how the science teaching courses have evolved in the schools and the steps that were taken to improve teaching methods.